Cashew-Apple Fruit Growing in the Florida Home Landscape - John McLaughlin; Carlos F. Balerdi; Jonathan H. Crane (EDIS)
HS-1127, an 11-page illustrated fact sheet by John McLaughlin, Carlos Balerdi, and Jonathan Crane, describes this tropical fruit, suitable climate for optimum growth, propagation, production and spacing for the home landscape, soils, planting, care, and pruning, harvest, ripening, storage, and use and nutritional value of the cashew apple. Includes references. Published by the UF Department of Horticultural Sciences, April 2008.